EFEITOS DE DISSIPAÇÃO E RUÍDO NO MODELO DE ONDAS DE DERIVA - Oyarzabal, Ricardo Sovek (2017)
We investigated chaotic transport of particles in a magnetized plasma with two waves of electrostatic drift. Considering the dissipation, we verify the appearance of periodic attractors and show that the properties of the basin depend on the dissipation. The average escape time of the initial conditions of an established frontier obeys a power law decay type with increasing of the dissipation. We find positive finite time Lyapunov exponents in dissipative drift motion, consequently the trajectories exhibit transient chaotic transport. The increase in noise dissipative drift motion enhances escape peaks in the average time for a given critical value of the noise intensity. The optimization of a system feature is the situation that occurs stochastic resonance (SR). It is observed that the noise changes the distribution in the escape time. This work is important to improve the understanding of the drift wave model in the presence of dissipation and noise, a natural ingredient in the environment of this kind of physical problem.